Thermal comfort modelling for indoor environment of smart buildings - Toh, Ming Hwee (2017)
This project aims to develop a model to model thermal comfort, and to determine the conditions required to achieve thermal comfort. Achieving thermal comfort have always been the aim of building owners and managers, as research have shown a positive relationship between thermal comfort and productivity of the occupants. Furthermore, doing so will also help to optimise energy and resource usage as over allocation of resources and energy to achieve thermal comfort can be prevented. Thermal comfort is affected by several factors, they can be categorised into two main groups. They are environmental and personal factors. Environmental factors can include but not limited to the air temperature, radiant temperature, air velocity and humidity level. While personal factors can include but not limited to the clothing worn and the activity being carried out by the subject. Thermal comfort is also defined by ASHRAE as “The condition of mind which expresses satisfaction with the thermal environment and is assessed by subjective evaluation”, this means that thermal comfort is something that is intangible, and may differ among subjects in the same thermal environment. This further increases the challenge of the modelling of thermal comfort. The thermal comfort model must take into account of both the environment and personal factors on top of the behaviour of humans. To design the model, a clear understanding of thermodynamics is also required. A thermal comfort model is developed in this project, providing us with the conditions required for thermal comfort, keeping energy efficiency in mind. After testing the model, we have concluded that the model does have its limitations, but the overall performance of the model in terms of its accuracy and robustness can be said to be satisfactory. Further studies are also recommended in this report for improvement on the thermal comfort model.